Visualizing synaptic plasticity in vivo by large-scale imaging of endogenous AMPA receptors - Graves, Austin R; Roth, Richard H; Tan, Han L; Zhu, Qianwen; Bygrave, Alexei M; Lopez-Ortega, Elena; Hong, Ingie; Spiegel, Alina C; Johnson, Richard C; Vogelstein, Joshua T; Tward, Daniel J; Miller, Michael I; et al. (eLife, 2021)
Elucidating how synaptic molecules such as AMPA receptors mediate neuronal communication and tracking their dynamic expression during behavior is crucial to understand cognition and disease, but current technological barriers preclude large-scale exploration of molecular dynamics in vivo. We have developed a suite of innovative methodologies that break through these barriers: a new knockin mouse line with fluorescently tagged endogenous AMPA receptors, two-photon imaging of hundreds of thousands of labeled synapses in behaving mice, and computer vision-based automatic synapse detection. Using these tools, we can longitudinally track how the strength of populations of synapses changes during behavior. We used this approach to generate an unprecedentedly detailed spatiotemporal map of synapses undergoing changes in strength following sensory experience. More generally, these tools can be used as an optical probe capable of measuring functional synapse strength across entire brain areas during any behavioral paradigm, describing complex system-wide changes with molecular precision.
Keywords: synapse; plasticity; in vivo imaging; AMPA receptor; behavior